Health Inequity by Design: Waiting Rooms and Patient Stress - Lamb, Matthew D. (Frontiers in Communication, 2021)
Little attention has been paid to health inequities designed into the physical spaces themselves. Clearly design is an important part of patient care. Design is simultaneously a complex system itself while existing as part of a larger complex (healthcare) system. For example, it is not enough to say that a patient experiences more stress because she/he is being treated in a hospital in a lower income area. The key, here, is that evidence demonstrates design as an important component, systemically, in healthcare. We know this to be true and base re-design efforts on this fact; but only in certain places. The central addition of this study is to point out that hospitals in higher income areas utilize the waiting room's ecology and its influence on patient stress and care. Efforts to intervene, through design, in waiting room ecology have consequences to equitable access to healthcare. Therefore, this study examines the implications of health inequalities designed-into physical space. Additionally, this study seeks to forefront “the interplay between communication and health, as well as how health is shaped and maintained” (Parrish-Sprowl, 2020). Thus, the purpose of this paper is to investigate, but also articulate, the ways design decisions impact people unequally and perpetuate health inequalities. To do so, this study investigates the communication ecologies of waiting rooms and their influence on patient stress, health equity, and elucidate under-examined systemic components of social determinants of health.